Cost-effectiveness of dual maternal HIV and syphilis testing strategies in high and low HIV prevalence countries: a modelling study. Issue 1 (January 2021) - Rodriguez, Patricia J; Roberts, D Allen; Meisner, Julianne; Sharma, Monisha; Owiredu, Morkor Newman; Gomez, Bertha; Mello, Maeve B; Bobrik, Alexey; Vodianyk, Arkadii; Storey, Andrew; Githuka, George; Chidarikire, Thato; et al.
Summary: Background: Dual HIV and syphilis testing might help to prevent mother-to-child transmission (MTCT) of HIV and syphilis through increased case detection and treatment. We aimed to model and assess the cost-effectiveness of dual testing during antenatal care in four countries with varying HIV and syphilis prevalence. Methods: In this modelling study, we developed Markov models of HIV and syphilis in pregnant women to estimate costs and infant health outcomes of maternal testing at the first antenatal care visit with individual HIV and syphilis tests (base case) and at the first antenatal care visit with a dual rapid diagnostic test (scenario one). We additionally evaluated retesting during late antenatal care and at delivery with either individual tests (scenario two) or a dual rapid diagnosis test (scenario three). We modelled four countries: South Africa, Kenya, Colombia, and Ukraine. Strategies with an incremental cost-effectiveness ratio (ICER) less than the country-specific cost-effectiveness threshold (US$500 in Kenya, $750 in South Africa, $3000 in Colombia, and $1000 in Ukraine) per disability-adjusted life-year averted were considered cost-effective. Findings: Routinely offering testing at the first antenatal care visit with a dual rapid diagnosis test was cost-saving compared with the base case in all four countries (ICER: –$26 in Kenya, –$559 in South Africa, –$844 in Colombia, and –$454 in Ukraine). Retesting during late antenatal care with a dual rapid diagnostic test (scenario three) was cost-effective compared with scenario one in all four countries (ICER: $270 in Kenya, $260 in South Africa, $2207 in Colombia, and $205 in Ukraine). Interpretation: Incorporating dual rapid diagnostic tests in antenatal care can be cost-saving across countries with varying HIV prevalence. Countries should consider incorporating dual HIV and syphilis rapid diagnostic tests as the first test in antenatal care to support efforts to eliminate MTCT of HIV and syphilis. Funding: WHO, US Agency for International Development, and the Bill & Melinda Gates Foundation.